Profitability, Valuation, and Stock Prices in Indonesian Banking Stocks: A Panel Data Analysis of IDX30 Firms - Agnes Ratna Wijayanti; Dradjad H Wibowo; Muhammad Iqbal (Dinasti Publisher, 2025)
This study examines the effect of Return on Assets (ROA), Price to Book Value (PBV), and Earnings Per Share (EPS) on the stock prices of banking companies included in the IDX30 during the 2019–2024 period. The study employs a quantitative approach using panel data regression based on secondary data obtained from the Indonesia Stock Exchange, company annual reports, and supporting market data. The results show that ROA has a positive and significant effect on stock prices, indicating that investors place strong emphasis on profitability efficiency in valuing banking stocks. In contrast, PBV and EPS have positive but statistically insignificant effects on stock prices. However, ROA, PBV, and EPS simultaneously have a significant effect on stock prices. These findings suggest that, in the context of large and liquid banking firms in Indonesia, profitability represented by ROA serves as the most credible financial signal for investors compared with valuation and per-share earnings indicators. This study contributes updated evidence from the post-pandemic period and highlights the importance of firm fundamentals in explaining stock-price movements in the Indonesian banking sector.